Scaling Up Access to Electricity : The Case of Rwanda - Baringanire, Paul; Malik, Kabir; Ghosh Banerjee, Sudeshna (World Bank, Washington, DC, 2014)
This knowledge note is the third of three case studies that concerns scaling up access to electricity in Africa, Bangladesh, and Rwanda. Rwanda s rapid achievements in expanding access to electricity after 2009 were made possible by one of the first applications of a sector-wide approach (SWAp) in the electricity sector. The World Bank played a pivotal role in the operationalization of the SWAp, first by assisting in the formulation of an investment prospectus that laid the groundwork for technical, financial, and implementation planning. The Rwandan experience is instructive for countries considering the adoption of a similar approach, particularly those starting from a low base. Rwanda's experience with electrification is an interesting case of how access to electricity can be quickly scaled up despite deficits in infrastructure and institutional capacity. In all, the SWAp in Rwanda delivered tremendous improvements in electricity access over a relatively short period of time. Although challenges remain, the program is on its way to achieving even the ambitious targets set for 2017 under the EARP II. Rwanda s experience has showed that with government ownership and alignment with national priorities, using SWAps in the electricity sector is a viable and attractive alternative to traditional project-based support.